Volatile fatty acid and aldehyde abundances evolve with behavior and habitat temperature in Sceloporus lizards. (20th May 2020) - Campos, Stephanie M; Pruett, Jake A; Soini, Helena A; Zúñiga-Vega, J Jaime; Goldberg, Jay K; Vital-García, Cuauhcihuatl; Hews, Diana K; Novotny, Milos V; Martins, Emília P
Abstract: Animal signals evolve by striking a balance between the need to convey information through particular habitats and the limitations of what types of signals can most easily be produced and perceived. Here, we present new results from field measures of undisturbed behavior and biochemical analyses of scent marks from 12 species of Sceloporus lizards to explore whether evolutionary changes in chemical composition are better predicted by measures of species behavior, particularly those associated with visual displays, chemoreception, and locomotion, or by measures of habitat climate (precipitation and temperature). We found that more active lizard species used fewer compounds in their volatile scent marks, perhaps conveying less specific information about individual and species identity. Scent marks from more active lizard species also had higher proportions of saturated fatty acids, and the evolution of these compounds has been tracking the phylogeny closely as we would expect for a metabolic byproduct. In contrast, the proportions of unsaturated fatty acids were better explained by evolutionary shifts in habitat temperature (and not precipitation), with species in warmer climates using almost no volatile unsaturated fatty acids. The proportion of aldehydes was explained by both behavior and environment, decreasing with behavioral activity and increasing with habitat temperature. Our results highlight the evolutionary flexibility of complex chemical signals, with different chemical compounds responding to different elements of the selective landscape over evolutionary time. Abstract : Scent marks are associated with animal habitats and behavior, and different species use scent marks differently. Our study of 12 species of Sceloporus lizards found that more active species use less informative scent marks, having fewer chemical compounds, and more saturated fatty acids, a metabolic byproduct. Active species likely rely more on visual displays than on scent marks. Climate also plays a role because species in warmer regions use fewer unsaturated fatty acids and aldehydes.